Jakość życia pacjentów leczonych systemowo z powodu raka płuca = The quality of life of patients treated with systemic due to lung cancer - Gajewska, Natalia; Szadowska-Szlachetka, Zdzisława; Rząca, Marcin Stanisław; Gutek, Anastazja; Gawron, Żaneta; Gujska, Dominika; Stanisławek, Andrzej (Journal of Education, Health and Sport, 2016)
Gajewska Natalia, Szadowska-Szlachetka Zdzisława, Rząca Marcin Stanisław, Gutek Anastazja, Gawron Żaneta, Gujska Dominika, Stanisławek Andrzej. Jakość życia pacjentów leczonych systemowo z powodu raka płuca = The quality of life of patients treated with systemic due to lung cancer. Journal of Education, Health and Sport. 2016;6(12):520-535. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.209579 http://ojs.ukw.edu.pl/index.php/johs/article/view/4081 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.12.2016. Revised 12.12.2016. Accepted: 19.12.2016. Jakość życia pacjentów leczonych systemowo z powodu raka płuca The quality of life of patients treated with systemic due to lung cancer Natalia Gajewska, Zdzisława Szadowska-Szlachetka, Marcin Stanisław Rząca, Anastazja Gutek, Żaneta Gawron, Dominika Gujska, Andrzej Stanisławek Natalia Gajewska Oddział Hematologii, Onkologii i Transplantologii Dziecięcej, Uniwersytecki Szpital Dziecięcy w Lublinie University Children’s Hospital in Lublin, Department: of Hematology , Oncology and Transplantation Children Studenckie Koło Naukowe, Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Uniwersytet Medyczny w Lublinie Poland Zdzisława Szadowska-Szlachetka Zakład Onkologii, Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Uniwersytet Medyczny w Lublinie Department of Oncology, Chair of Oncology and Enviromental Health, Medical University of Lublin Poland Marcin Stanisław Rząca Zakład Onkologii, Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Uniwersytet Medyczny w Lublinie Poland Principal contact for editorial correspondence. Anastazja Gutek Studenckie Koło Naukowe, Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Uniwersytet Medyczny w Lublinie Students scientific association, Chair of Oncology and Enviromental Health, Medical University of Lublin Poland Żaneta Gawron Oddział Otolaryngologii Dziecięcej, Foniatrii i Audiologii, Uniwersytecki Szpital Dziecięcy w Lublinie University Children’s Hospital in Lublin. Department of Pediatric Otolaryngology , Audiology and Phoniatrics Studenckie Koło Naukowe, Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Uniwersytet Medyczny w Lublinie Students scientific association, Chair of Oncology and Enviromental Health, Medical University of Lublin Poland Dominika Gujska Studenckie Koło Naukowe, Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Uniwersytet Medyczny w Lublinie Students scientific association, Chair of Oncology and Enviromental Health, Medical University of Lublin Poland Andrzej Stanisławek Zakład Onkologii, Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Uniwersytet Medyczny w Lublinie Department of Oncology, Chair of Oncology and Enviromental Health, Medical University of Lublin Centrum Onkologii Ziemi Lubelskiej im. Św. Jana z Dukli, Oddział Chirurgii Onkologicznej St. John’s Cancer Center Lublin, Surgical Oncology Poland Streszczenie Wstęp Rak płuca jest przyczyną największej ilości zgonów wśród pacjentów onkologicznych w krajach wysokorozwiniętych a 5-letnie przeżycie leczonych z powodu tego nowotworu dotyczy zaledwie 10-14%. Pacjenci często poddawani są leczeniu systemowemu, którego działania niepożądane pogarszają ich jakość życia. Metody badań i cel badań Kwestionariuszami QLQ – C30 i QLQ – L13 przebadano 111 pacjentów leczonych cytostatykami z powodu raka płuc w Samodzielnym Publicznym Szpitalu Klinicznym nr 4 w Lublinie. Wyniki Problemy z wykonywaniem męczących czynności występował u wszystkich badanych. U niemal wszystkich- (94%) występowały ograniczenia w wykonywaniu codziennych czynności i zmęczenie - (98%). Napięcie psychiczne odczuwała większość badanych- (79%). Duszność spoczynkowa występowała u 47% badanych a kaszel bardzo często u 41%. Najwięcej badanych subiektywnie swój stan zdrowia i jakość życia oceniło na poziomie przeciętnym. Wnioski Funkcjonowanie fizyczne, poznawcze, emocjonalne i społeczne obniżało się wraz z wiekiem chorych leczonych chemioterapią. Ból występował u wszystkich badanych. Zaburzenia snu istotnie częściej dotyczyły kobiet niż mężczyzn. Pogorszone funkcjonowanie w rolach społecznych istotnie częściej było dostrzegane przez mieszkańców miast niż wsi. Najczęściej występującym i najbardziej uciążliwym objawem ze strony układu oddechowego było uczucie duszności podczas wchodzenia po schodach. Słowa kluczowe: rak płuc, jakość życia, chemioterapia, objawy Summary Introduction Lung cancer is the cause of the largest amount of deaths among cancer patients in highly developed countries and a 5-year-survival of people treated for this tumor is only 10-14%. Patients often undergo systemic treatment, the side effects of which worsen their quality of life. Test methods and purpose of the study 111 patients treated with cytostatics for lung cancer in Samodzielny Publiczny Szpital Kliniczny nr 4 w Lublinie (Independent Public Clinical Hospital No. 4 in Lublin) were tested using QLQ – C30 and QLQ – L13 Questionnaires. Results Problems with the performance of fatiguing activities occurred in all respondents. In almost all respondents - (94%), there were limitations in performance of everyday life activities or fatigue - (98%). Mental tension was felt by the majority of respondents - (79%). Resting dyspnea occurred in 47% of respondents and the cough occurred very often in 41%. Most respondents subjectively assessed their health and quality of life on an average level. Conclusions Physical, cognitive, emotional and social functioning decreased with age of patients treated with chemotherapy. Pain was felt by all patients. Sleep disorders significantly more often related to women than men. Impaired functioning in social roles was significantly more often perceived by urban residents than rural ones. The most common and most troublesome symptom within the frameworks of the respiratory system was shortness of breath when climbing stairs. Key words: lung cancer, quality of life, chemotherapy, symptoms